2022
DOI: 10.4081/jphr.2021.2551
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hydraulic Fracturing Activities on Birth Outcomes are Evident in a Non-Individualized County-Wide Aggregate Data Sample from Colorado

Abstract: Background: There is growing concern about the recent increase in oil and gas development using hydraulic fracturing. Studies linking adverse birth outcomes and maternal proximity to hydraulic fracturing wells exist but tend to use individualized maternal and infant data contained in protected health care records. In this study, we extended the findings of these past studies to evaluate if analogous effects detected with individualized data could be detected from non-individualized county-wide aggregated data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Our results align with other studies that found associations between exposure to NGD production with decreased birth weight ( Apergis et al, 2019 , Cushing et al, 2020 , Deziel et al, 2020 , Tran et al, 2020 , Tran et al, 2021 , Willis et al, 2021 ), and increased risk of infants born LBW ( Apergis et al, 2019 , Deziel et al, 2020 , Tran et al, 2020 , Tran et al, 2021 ), or SGA ( Deziel et al, 2020 , Tran et al, 2020 , Tran et al, 2021 ). However, in others, associations have been mixed ( Cushing et al, 2020 , Erickson et al, 2021 ). Our results were inconsistent with prior literature that has reported a positive association between exposure to NGD production and preterm birth ( Cushing et al, 2020 , Deziel et al, 2020 , Gonzalez et al, 2020 , Tran et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our results align with other studies that found associations between exposure to NGD production with decreased birth weight ( Apergis et al, 2019 , Cushing et al, 2020 , Deziel et al, 2020 , Tran et al, 2020 , Tran et al, 2021 , Willis et al, 2021 ), and increased risk of infants born LBW ( Apergis et al, 2019 , Deziel et al, 2020 , Tran et al, 2020 , Tran et al, 2021 ), or SGA ( Deziel et al, 2020 , Tran et al, 2020 , Tran et al, 2021 ). However, in others, associations have been mixed ( Cushing et al, 2020 , Erickson et al, 2021 ). Our results were inconsistent with prior literature that has reported a positive association between exposure to NGD production and preterm birth ( Cushing et al, 2020 , Deziel et al, 2020 , Gonzalez et al, 2020 , Tran et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple challenges in comparing this body of research related to methodological inconsistencies involving measurement of NGD production type, distance, and intensity of exposure. Similar to our approach, some studies have included both conventional and unconventional NGD ( Apergis et al, 2019 , Cushing et al, 2020 , Deziel et al, 2020 , Gonzalez et al, 2020 , Tran et al, 2020 , Willis et al, 2021 ), while others have focused on fracked wells ( Erickson et al, 2021 , Tran et al, 2021 ), or also included inactive wells ( Tran et al, 2020 ). We considered a woman to be exposed if she lived in a county that contained any NGD production because county was the lowest geographical identifier available on the birth certificate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations